Analysis of morbidity and health care usage of patients with suspected thyroid disorders - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Kühlein, Thomas; Hueber, Susann (Preventing Overdiagnosis Congress 2019, 2019)
Objectives (150 words) In many countries the incidence of thyroid cancer increased in the last years, while thyroid cancer mortality remained stable. This is seen as an indicator for overdiagnosis. Furthermore, many surgically removed thyroid nodules turn out to be benign, especially in Germany. Germany has a highly fragmented health care system with easy access to diagnostic imaging even at the level of general practice. Most thyroid nodules are detected using sonography early in the work-up of suspected thyroid disorders, which might trigger control loops and invasive treatment. Thus, the objective of this study is to systematically analyze whether the early use of sonography in the work-up of suspected thyroid disease might lead in a cascade effect from overdiagnosis to overtreatment. The following research question will be answered: What effects does the early use of sonography in the diagnostic process of suspected thyroid disorders have on morbidity, health care utilization and costs? Method (150 words) To answer this research question a retrospective cohort-study design comparing two propensity-matched groups was chosen. Claims data of patients with statutory health insurance held by the Bavarian Association of Statutory Health Insurance Physicians were used. Early use of sonography was defined as having an initial TSH test followed by a sonography within 28 days. Patients having received a TSH test in 2012 were included and allocated to one of the two following groups: Group 1: TSH test followed by sonography of the thyroid within 28 days. Group 2: TSH test without sonography of the thyroid within 28 days. The two groups were matched for sociodemographic characteristics, morbidity, and reason for encounter using propensity score matching. The two groups are currently compared in terms of morbidity, health care utilization and costs. Results (150 words) After propensity score matching, the sample consisted of 68,862 patients in each group. Data analysis is not completed yet. The results will be available for presentation until the conference. Conclusions (150 words) Early use of sonography in the work-up of suspected thyroid disorders might trigger a cascade of overdiagnosis and overtreatment. By systematically analyzing clinical pathways of patients with suspected thyroid disorders and the resulting medical and economic consequences, we hope to contribute to the identification and reduction of overdiagnosis and overtreatment concerning thyroid disorders. The project is embedded in the PRevention of Overdiagnosis in PRImary CARE (PRO PRICARE) research network funded by the German Federal Ministry of Research and Education. </

Consequences of early thyroid ultrasound on subsequent tests, morbidity and costs: an explorative analysis of routine health data from German ambulatory care - Hueber, Susann; Biermann, Valeria; Tomandl, Johanna; Warkentin, Lisette; Schedlbauer, Angela; Tauchmann, Harald; Klemperer, David; Lehmann, Maria; Donnachie, Ewan; Kühlein, Thomas (BMJ Open, 2023)
Objectives This study aims to evaluate whether the use of thyroid ultrasound (US) early in the work-up of suspected thyroid disorders triggers cascade effects of medical procedures and to analyse effects on morbidity, healthcare usage and costs. Study design Retrospective analysis of claims data from ambulatory care (2012-2017). Setting Primary care in Bavaria, Germany, 13 million inhabitants. Participants Patients having received a thyroid stimulating hormone (TSH) test were allocated to (1) observation group: TSH test followed by an early US within 28 days or (2) control group: TSH test, but no early US. Propensity score matching was used adjusting for socio-demographic characteristics, morbidity and symptom diagnosis (N=41 065 per group after matching). Primary and secondary outcome measures Using cluster analysis, groups were identified regarding frequency of follow-up TSH tests and/or US and compared. Results Four subgroups were identified: cluster 1: 22.8% of patients, mean (M)=1.6 TSH tests; cluster 2: 16.6% of patients, M=4.7 TSH tests; cluster 3: 54.4% of patients, M=3.3 TSH tests, 1.8 US; cluster 4: 6.2% of patients, M=10.9 TSH tests, 3.9 US. Overall, reasons that explain the tests could rarely be found. An early US was mostly found in clusters 3 and 4 (83.2% and 76.1%, respectively, were part of the observation group). In cluster 4 there were more women, thyroid-specific morbidity and costs were higher and the early US was more likely to be performed by specialists in nuclear medicine or radiologists. Conclusion Presumably unnecessary tests in the field of suspected thyroid diseases seem to be frequent, contributing to cascades effects. Neither German nor international guidelines provide clear recommendations for or against US screening. Therefore, guidelines on when to apply US and when not are urgently needed.
CRIS-Team Scopus Importer:2023-03-24
Keywords: PRIMARY CARE; Thyroid disease; ULTRASONOGRAPHY

Development of a subset of the international classification of functioning, disability and health as a basis for a questionnaire for community-dwelling older adults aged 75 and above in primary care: a consensus study - Rink, Laura; Tomandl, Johanna; Womser, Sonja; Kühlein, Thomas; Sebastiao, Maria (BMJ Open, 2023)
Objectives Functioning of older adults needs to be adequately described before it can become the focus of care. The International Classification of Functioning, Disability and Health (ICF) provides a basis for describing functioning. As the ICF is too extensive for daily practice in primary care, there is a need for a reduced number of categories. The aim is to develop an ICF-subset for community-dwelling older adults aged 75 and above in primary care. Design The scientific basis for decision-making in our consensus study was laid by four preparatory studies, identifying potentially relevant ICF categories from four perspectives (research, patients', experts' and clinical perspective). The results of the preparatory phase were discussed by an international expert panel in a consensus study following the Nominal Group Technique (NGT). Setting An international 1-day online consensus conference. Participants International experts (n=7) participated in the consensus conference, meeting the following criteria: extensive expertise in the field of the ICF and/or caring for older adults, and being fluent in English. Results Each preparatory study yielded a different number of categories with some overlaps but also differences. The expert panel decided to: (1) restrict the subset to second-level categories and reduce the number of categories from the preparatory phase, (2) limit the subset to the component activities and participation and (3) weight the patients' perspective as the most relevant one. Conclusions By using consensus techniques and the NGT, the process led to 51 second-level ICF categories to describe the functioning of community-dwelling older adults. The decisions made in the consensus conference emphasised the importance of considering the individual life situation from a more holistic perspective and addressing functioning as a focus of care. Next, the 51 categories will contribute to the development of an ICF-based questionnaire.
CRIS-Team Scopus Importer:2023-09-15
Keywords: decision making; geriatric medicine; primary care; qualitative research

Kosteneffekte durch nicht indizierte Diagnostik der Schilddrüse - Hafner, Lucas; Tomandl, Johanna; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hoyer, Stefanie; Hueber, Susann; Donnachie, Ewan; Kühlein, Thomas (Deutsche Gesellschaft für Gesundheitsökonomie 11. Jahrestagung Gesundheitsverhalten und Prävention, 2019)
Einleitung Die Inzidenz von Schilddrüsenkarzinomen ist bei konstanter Mortalität in jüngerer Vergangenheit in Deutschland stark angestiegen. Dies ist vermutlich auf verbesserte Diagnosemöglichkeiten, die zur Entdeckung zahlreicher kleiner Schilddrüsenknoten führt, die unerkannt nie als medizinisches Problem in Erscheinung getreten wären. Wir untersuchen, ob nicht indizierte Diagnostik im Schilddrüsenkontext zu invasiven Behandlungen und infolge dessen hohen Kosten führt. Konkret untersuchen wir, ob sich durch eine nicht indizierte Sonographie der Schilddrüse die ambulanten, stationären sowie pharmazeutischen Gesundheitskosten bei den betroffenen Patienten kurz und langfristig erhöhen. Methoden Auf Basis von Routinedaten aus Deutschland werden Gesundheitskostenverläufe von Patienten untersucht, deren Symptomatik zu Beginn der Studie auf eine Fehlfunktion der Schilddrüse hindeuten. Bei allen betrachteten Patienten wurde zunächst per Blutuntersuchung der TSH-Wert bestimmt, mit dessen Hilfe Anomalien der Schilddrüsenfunktion identifiziert werden können. Als Interventionsgruppe werden die Patienten betrachtet, bei denen nicht leitliniengerecht, d.h. mit nur kurzem zeitlichen Abstand, zusätzlich eine Sonographie der Schilddrüse durchgeführt wird. Als Kontrollgruppe gelten Patienten ohne oder mit leitlinienkonformer Sonographie. Um mögliche Kosteneffekte der nicht leitliniengerechten Sonographie messen zu können, wird mittels eines Matching-Verfahren sichergestellt, dass sich beide Gruppen hinsichtlich Alter, Geschlecht, Wohnort, ambulantem Behandlungsanlass sowie Morbidität nicht unterscheiden. Ergebnisse Die durchschnittlichen Kosten für schilddrüsenspezifische ambulante Leistungen sowie schilddrüsenspezifische Arzneimittel sind in der Interventionsgruppe signifikant höher als in der Kontrollgruppe. Dieser Unterschied ist auch noch mehrere Jahre nach der Intervention zu beobachten. Allerdings ist der Anteil der schilddrüsenspezifischen Kosten an den Gesamtkosten in beiden Gruppen sehr gering. Hinsichtlich der durchschnittlichen Gesamtkosten (ambulant, stationär und pharmazeutisch) zeigen sich im Analysezeitraum keine signifikant unterschiedlichen Verläufe bei Interventions- und Kontrollgruppe. Fazit Unsere Ergebnisse liefern keine Evidenz dafür, dass eine nicht indizierte Sonographie der Schilddrüse Behandlungskaskaden auslöst, welche zu hohen allgemeinen Gesundheitskosten führt. Lediglich schilddrüsenspezifische Kosten sind nach der nicht indizierten Diagnostik selbst langfristig höher. Im Hinblick auf die Gesamtkosten fällt dieser Kostenunterschied allerdings nicht ins Gewich
Keywords: Gesundheitsökonomische Evaluation; Medizinische Überversorgung; Schilddrüsenerkrankungen

Kritische Reflexion zur Nutzung von GKV Routinedaten in der Versorgungsforschung - Tomandl, Johanna; Worm, Lukas; Biermann, Valeria; Hueber, Susann (53. Kongress für Allgemeinmedizin und Familienmedizin, 2019)
Hintergrund Das Heranziehen von Routinedaten gesetzlicher Krankenversicherungen in der Versorgungsforschung nimmt rasant zu. Die Vorteile dieser Daten bestehen unter anderem darin, dass sie die tatsächlichen Behandlungsverläufe widerspiegeln, unselektiert sind und eine eigene Datenerhebung entbehrlich machen. Da Routinedaten zu Abrechnungs- und nicht zu Forschungszwecken erhoben werden, bringt die Nutzung dieser Daten in der Forschung einige Herausforderung mit sich. Fragestellung Welche Faktoren müssen bei der Verwendung von Routinedaten zu Forschungszwecken berücksichtigt werden? Methoden Es werden typische Herausforderungen in der Routinedatenanalyse anhand eines aktuell laufenden Projekts zum Thema Überversorgung bei Schilddrüsenpatienten dargestellt und kritisch reflektiert. Ergebnisse Aufgrund des enormen Umfangs verfügbarer Daten (z.B. ambulante und stationäre Leistungen, Erkrankungen, Arzneimitteldaten, Arbeitsunfähigkeit) müssen Fragestellung sowie relevante Outcomes präzise definiert sein. Für die Datenaufbereitung der primär zu Abrechnungszwecken erhobenen Daten muss ausreichend Zeit eingeplant werden. Es empfiehlt sich eine enge Zusammenarbeit mit den Dateneignern sowie verschiedenen Disziplinen (z.B. Medizin, Statistik, Gesundheitsökonomie). Aussagen zur Versorgungsqualität sind nur eingeschränkt möglich, da lediglich abrechnungsrelevante Daten dokumentiert werden (somit keine Angaben z.B. zu Laborergebnissen oder Schweregrad vorliegen) und der Zusammenhang zwischen erbrachten Leistungen (tagesgenau dokumentiert) und gestellten Diagnosen (quartalsweise dokumentiert) nicht direkt herstellbar ist. Diskussion Anhand von Routinedaten können Behandlungsverläufe und Versorgungsmuster sowie erbrachte Leistungen, Morbidität und Kosten abgebildet werden. Aussagen zur Versorgungsqualität können nur annäherungsweise erfolgen. Eine engere Verzahnung von Primär- und Sekundärforschung kann hier Abhilfe schaffen. Take Home Message für die Praxis Routinedaten stellen eine zunehmend wichtige Datenquelle in der Versorgungsforschung dar. Jedoch muss die Eignung der Daten unter Berücksichtigung der genannten Limitationen für jede Fragestellung gründlich abgewogen werde
Keywords: Routinedaten; Methoden; Symposium; Methodenreflexion

Laying the foundation for a core set of the International Classification of Functioning, Disability and Health for community-dwelling adults aged 75 years and above in general practice: a study protocol - Tomandl, Johanna; Book, Stephanie; Gotthardt, Susann; Heinmüller, Stefan; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Hoyer, Stefanie (BMJ Open, 2018)
Introduction With the medical focus on disease, the problem of overdiagnosis inevitably increases with ageing. Considering the functional health of patients might help to discriminate between necessary and unnecessary medicine. The International Classification of Functioning, Disability and Health (ICF) is an internationally recognised tool for describing functional health. However, it is too detailed to be used in primary care practices. Consequently, the aim of this study is to identify relevant codes for an ICF core set for community-dwelling older adults (75 years and above) in primary care. Methods and analysis The study will follow the methodology proposed by the ICF Research Branch to identify relevant concepts from different perspectives: (1) Research perspective: A systematic review of studies focusing on functional health in old age will be conducted in different databases. Relevant concepts will be extracted from the publications. (2) Patients' perspective: Relevant areas of functioning and disability will be identified conducting qualitative interviews and focus groups with community-dwelling older persons. The interviews will be transcribed verbatim and analysed using the documentary method of interpretation. (3) Experts' perspective: An online survey with open-ended questions will be conducted. Answers will be analysed using the qualitative content analysis of Mayring. (4) Clinical perspective: A cross-sectional empirical study will be performed to assess the health status of community-dwelling older adults using the extended ICF checklist and other measurement tools. Relevant concepts identified in each study will be linked to ICF categories resulting in four preliminary core sets. Ethics and dissemination Ethical approval for the study was obtained (90_17B). All participants will provide written informed consent. Data will be pseudonymised for analysis. Results will be disseminated by conference presentations and journal publications. Trial registration number Projektdatenbank Versorgungsforschung Deutschland: VfD_17_003833, Clinicaltrials.gov: NCT03384732 and PROSPERO: CRD42017067784.
EVALuna2:35588

Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: Relevant categories of their functioning from the research perspective, a scoping review - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann (BMJ Open, 2021)
Objectives The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting Home, primary care. Participants Community-dwelling adults aged 75 years and above. Results From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the â € activities and participation' component. The most frequently identified categories were â € memory functions', â € dressing' and â € changing basic body position'. Conclusions This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-05
Keywords: general medicine (see internal medicine); geriatric medicine; primary care

Laying the foundation for an ICF core set for community dwelling older adults in primary care: an expert survey Entwicklung eines ICF-Core-Sets für ältere Patienten in der Hausarztpraxis: eine Expertenumfrage - Gotthardt, Susann; Tomandl, Johanna; Höfle, Anina; Kühlein, Thomas; Book, Stephanie; Graessel, Elmar; Talaska, Michael; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: A holistic biopsychosocial model focused on functioning in individual contexts (environment, task) is better suited to meet the needs of older patients than disease only based models. The International Classification of Functioning, Disability and Health (ICF) is the official standard for describing functional health. As the ICF is too detailed to be used in practice, brief core sets have been developed. Objective: This study aimed to identify relevant aspects of functioning for older primary care patients from the perspective of healthcare professionals in Germany. Material and methods: An internet-based cross-sectional expert survey was conducted in preparation for the development of an ICF core set for community-dwelling patients aged 75 years and older. Open-ended questions to identify the most important aspects of functioning and disability in old age were used. Responses were analyzed based on a content analysis approach to identify relevant concepts in the care of the target population. These concepts were then linked to ICF categories according to established linking rules. Results: A total of 63 experts participated in this survey. Across all responses, 2240 meaningful concepts were identified. A total of 75 ICF categories (4 first level categories, 67 second level categories, 4 code combinations) were identified by at least 5% of respondents and will thus be considered as candidate categories for the final ICF core set. Most of concepts were associated with the environmental factors component. The most frequently identified categories were immediate family and family relationships. Conclusion: This survey provides a list of relevant ICF categories from the experts’ perspective and together with other preparatory studies will be used for developing an ICF core set for community-dwelling older adults in primary care.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Community-dwelling older patients; Expert survey; Functioning; ICF core set; Primary care

Laying the foundation for an International Classification of Functioning, Disability and Health Core Set for community-dwelling elderly adults in primary care: the clinical perspective identified in a cross-sectional study - Book, Stephanie; Ulbrecht, Gudrun; Tomandl, Johanna; Kühlein, Thomas; Gotthardt, Susann; Freiberger, Ellen; Grässel, Elmar (BMJ Open, 2020)
OBJECTIVES: Having more information about the biopsychosocial functioning of their geriatric patients might help physicians better balance medical interventions according to patients' needs. For this reason, we aimed to develop an easy-to-handle International Classification of Functioning, Disability and Health (ICF) Core Set for community-dwelling geriatric patients aged 75 and older in primary care. In this empirical study, we describe the functioning and health of community-dwelling patients aged 75 and older in primary care in Germany and identify the most common problems encountered by these individuals when using the ICF. DESIGN: In this exploratory, cross-sectional study, a health professional conducted semi-structured interviews. SETTING: Community-dwelling older adults aged 75 and older in Germany. PARTICIPANTS: 65 participants (mean age=80.2, SD=3.6). OUTCOME MEASURES: Extended ICF Checklist V.2.1a, patients prioritised chapters of the 'activities and participation' component. RESULTS: The three most common impairments for 'body functions' were visual system functions (ICF-code b210; 89%), blood pressure functions (b420; 80%) and sensations associated with hearing and vestibular functions (b240; 59%). For 'body structures', they were eyes, ears and related structures (s2; 81%), structure of mouth (s320; 74%) and structures related to the digestive, metabolic and endocrine systems (s5; 49%). For the 'activities and participation' component, adequate aids compensated for activity limitations to a certain degree. Still, after having adequate aids, the category in which the participants had the most difficulty was walking (d450; 35%). Participants rated the 'mobility' chapter as the most important of all chapters. 'Environmental factors' were facilitators of participants' functioning. CONCLUSIONS: This empirical study provides a list of ICF categories relevant to older adults from the clinical perspective. Along with lists from the other three preparatory studies, it will form the basis for the development of an ICF Core Set for community-dwelling older adults in primary care. TRIAL REGISTRATION DETAILS: The trial is registered in ClinicalTrials.gov (NCT03384732).
CRIS-Team Scopus Importer:2020-12-04
Keywords: aging; community-dwelling older people; core set; functioning; general practice; ICF

Laying the foundation for a primary care core set of the international classification of functioning, disability and health (icf) for community-dwelling older adults: A qualitative study - Tomandl, Johanna; Book, Stephanie; Höfle, Anina; Grässel, Elmar; Sieber, Cornel; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Gotthardt, Susann (Journal of Rehabilitation Medicine, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring s qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community-dwelling elderly people, which will be used to develop a Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-26
Keywords: aged; cross-sectional study; Disability and Health; focus group; general practice/methods.; geriatric assessment/ methods; independent living; International Classification of Functioning; interviews as topic

Morbidität und Inanspruchnahme des Gesundheitswesens von PatientInnen mit Verdacht auf Schilddrüsenerkrankungen. Eine retrospektive Kohortenanalyse unter Verwendung von Routinedaten. - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hueber, Susann; Kühlein, Thomas (18. Deutscher Kongress für Versorgungsforschung, 2019)
Hintergrund In zahlreichen Ländern ist die Inzidenz von Schilddrüsenkarzinomen bei gleichbleibender Mortalität in den letzten Jahren rasant angestiegen. Dies wird als ein Indiz für Überdiagnostik gesehen. Die Entdeckung von Schilddrüsenknoten erfolgt häufig im Rahmen initial nicht indizierter Diagnostik, die dann Auslöser von Kontrollschleifen und letztlich invasiven Behandlungen sein kann. Gerade in Deutschland gibt es eine hohe Anzahl von Schilddrüsenoperationen, bei denen sich die entfernten Knoten in der anschließenden Histologie häufig als benigne herausstellen. Ziel unsere Studie ist die systematische Analyse, ob der frühzeitige Einsatz der Sonographie im Abklärungsprozess bei Verdacht auf Schilddrüsenerkrankungen in einer Art Kaskade von Überdiagnostik hin zu Übertherapie führt. Fragestellung Welche Auswirkungen hat der frühzeitige Einsatz der Schilddrüsen-Sonographie zur Abklärung von Schilddrüsenerkrankungen auf Morbidität und Inanspruchnahme des Gesundheitswesens bei den betroffenen PatientInnen? Methode Zur Beantwortung der Forschungsfrage wird aktuell eine retrospektive Kohortenanalyse mit Daten der Kassenärztlichen Vereinigung Bayerns (2012 bis 2017) durchgeführt. Untersucht werden Daten von PatientInnen mit und ohne nicht-indizierter Schilddrüsen-Sonographie. Nicht-indizierte Schilddrüsen-Sonographie wird definiert als erstmaliger TSH-Test gefolgt von einem Ultraschall der Schilddrüse innerhalb von 28 Tagen ohne Vorliegen einer Hypo- oder Hyperthyreose. Die beiden Gruppen wurden mittels Propensity Score Matching gematcht und bezüglich Morbidität und Inanspruchnahme des Gesundheitswesens untersucht. Ergebnisse Es werden Daten von 68.862 PatientInnen in jeder Gruppe ausgewertet. Die Datenanalyse ist noch nicht abgeschlossen. Die Ergebnisse werden zum Kongress vorliegen. Diskussion und praktische Implikationen Ein systematischer Vergleich verschiedener Behandlungspfade sowie deren medizinischer und ökonomischer Konsequenzen soll dazu beitragen, Überdiagnostik und Übertherapie zu identifizieren und zu beschreiben. Das Projekt wird im Rahmen des BMBF-geförderten Netzwerkes PRO PRICARE durchgeführt.
Keywords: Überversorgung; Schilddrüsenerkrankungen; Versorgungsforschung; Routinedaten; Kohortenanalyse

Short and medium-term cost effects of non-indicated thyroid diagnostics: Empirical evidence from German claims data - Hafner, Lucas; Biermann, Valeria; Donnachie, Ewan; Hueber, Susann; Kühlein, Thomas; Tauchmann, Harald; Tomandl, Johanna (European Journal of Health Economics, 2022)
This paper contributes to the discussion of whether non-indicated ultrasound examinations of the thyroid gland contribute to overtreatment and excess health care expenditures. Using two sources of claims data from Germany, we analyzed data from patients who underwent a TSH blood test which is the initial diagnostic measure to check for possible presence of thyroid dysfunction. In a matching analysis, we compared health costs of two groups of patients. One consisted of patients who underwent an early thyroid ultrasound that according to medical guidelines – at this point – was probably not indicated. The other group consisted of patients, who underwent no ultrasound examination at all or later in the course of the disease, making probable a correct indication. Both groups were made comparable by the means of a matching procedure. Average thyroid-specific health costs were substantially higher for the first group in the quarter in which the ultrasound examination took place. Some deviation in these specific costs persisted over a substantial period of time, with drug expenditures exhibiting the biggest difference. If, however, total health costs were considered, difference in costs was only found in the initial quarter. We conclude that non-indicated ultrasound examination of the thyroid gland may have some moderate effects on thyroid-specific costs. Yet the data do not suggest that long-lasting overtreatment and excess health expenditures are initiated by non-indicated ultrasound in German
Keywords: matching; health cost; non-indicated ultrasound; thyroid anomalies

The Information needs of internet users and their requirements for online health information - a scoping review of qualitative and quantitative studies - Wollmann, Katharina; van der Keylen, Piet; Tomandl, Johanna; Meerpohl, Joerg J.; Sofroniou, Mario; Maun, Andy; Voigt-Radloff, Sebastian (Patient Education and Counseling, 2021)
Objective This scoping review has been conducted to summarise the information needs of internet users and their requirements for online health information. Methods We searched MEDLINE, Web of Science and Scopus up to July 2019. Qualitative, quantitative and mixed-method studies were included and a thematic synthesis with category formation and exact description of the items was carried out. Results 118 studies were included. To address all users’ needs mentioned in the included studies, we grouped them into nine main categories: authority, comprehension, currency, evidence-based information, exchange with others, independence, purpose, services, user experience. The evaluation showed that website users wanted qualifications of authors to be cited. Users preferred health information that offered interactive elements and resources for relatives, whilst also providing an opportunity for online contact with others. The ease with which information was accessed and the intelligibility of texts were regarded as being very important to users. Conclusion Given the rapid evolvement and changes of online health information, it is crucial to provide up to date insights and a comprehensive overview of the range of criteria. Practice Implications With the results obtained through this scoping review, the creators of online health information could be assisted in providing user-specific resources.<br
Keywords: Information needs; internet users; online health information; scoping review

The Online Health Information Needs of Family Physicians: Systematic Review of Qualitative and Quantitative Studies - van der Keylen, Piet; Tomandl, Johanna; Wollmann, Katharina; Moehler, Ralph; Sofroniou, Mario; Maun, Andy; Voigt-Radloff, Sebastian; Frank, Luca (Journal of Medical Internet Research, 2020)
Background: Digitalization and the increasing availability of online information have changed the way in which information is searched for and retrieved by the public and by health professionals. The technical developments in the last two decades have transformed the methods of information retrieval. Although systematic evidence exists on the general information needs of specialists, and in particular, family physicians (FPs), there have been no recent systematic reviews to specifically address the needs of FPs and any barriers that may exist to accessing online health information.
CRIS-Team WoS Importer:2021-01-22

Überversorgung durch nicht-indizierten Ultraschall der Schilddrüse? Eine Analyse von Routinedaten der Kassenärztlichen Vereinigung Bayerns - Hueber, Susann; Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Lehmann, Maria; Schedlbauer, Angela; Gerlach, Roman; Tauscher, Martin; Donnachie, Ewan; Kühlein, Thomas (53. Kongress für Allgemeinmedizin und Familienmedizin (DEGAM), 2019)
Hintergrund Ein Ultraschallscreening auf Schilddrüsenerkrankungen bei symptomfreien Patienten gilt als möglicher Auslöser für Überversorgung, weshalb es nicht empfohlen wird. Wir vermuten, dass ein „graues“ Ultraschallscreening Kaskadeneffekte auslösen kann. Kaskadeneffekte sind definiert als eine Kette diagnostischer und therapeutischer Maßnahmen, die einmal begonnen nur schwer unterbrochen werden kann. Ziel unseres Projektes ist es, solche Kaskadeneffekte zu identifizieren und zu beschreiben. Fragestellung Welche Patienten sind von Kaskadeneffekten besonders betroffen? Gibt es Subgruppen mit unterschiedlichen Behandlungsverläufen? Wie unterscheiden sich diese Gruppen? Methoden Retrospektive Analyse eines Datensatzes der Kassenärztlichen Vereinigung Bayerns (2012 bis 2017). Untersucht werden Daten von Patienten mit nicht-indiziertem Schilddrüsen-Ultraschall, definiert als erstmaliger TSH-Test ohne die Diagnose einer Funktionsstörung, gefolgt von einem Ultraschall der Schilddrüse innerhalb von 28 Tagen. Um Subgruppen zu identifizieren wird eine Clusteranalyse nach der Häufigkeit von schilddrüsenspezifischen Untersuchungen im Zeitverlauf durchgeführt. Ergebnisse Es werden Daten von 41.065 Patienten ausgewertet. Erste Analysen lassen vermuten, dass es Subgruppen von Patienten gibt, die häufigen Kontrolluntersuchungen unterzogen werden. Die Datenanalyse ist noch nicht abgeschlossen. Vollständige Ergebnisse werden zum Kongress vorliegen. Diskussion Eine systematische Analyse und Darstellung von Überversorgungsprozessen, ausgelöst durch nicht-indizierte Untersuchungen, soll dazu beitragen, unnötige Medizin zu reduzieren. Das Projekt wird im Rahmen des BMBF-geförderten Netzwerkes PRO PRICARE durchgeführt. Take Home Message für die Praxis Die ersten Ergebnisse lassen vermuten, dass das Durchführen einer nicht indizierten Schilddrüsensonographie in bestimmen Patientengruppen zu Kaskadeneffekten und Überversorgung führen kan
Keywords: Überversorgung; Schilddrüse; Routinedaten; Versorgungsforschung